2019
DOI: 10.1111/jog.14183
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and influence of Mycoplasma/Ureaplasma cultures in amniotic fluid on perinatal outcomes

Abstract: Aim To investigate the effects of Mycoplasma/Ureaplasma cultured in amniotic fluid on perinatal characteristics in preterm delivery between 22 and 33 weeks of gestation. Methods The study was conducted in a tertiary perinatal center and involved 38 pregnant women who had undergone amniocentesis to evaluate intrauterine infection due to preterm labor or premature rupture of membranes. The subjects were divided into three groups based on the culture results: negative (Negative Group, n = 24), positive for Mycopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…and Mycoplasma spp. developed EONS in previous studies 25,26 and in our study. In some studies, 27–30 EONS developed in only Ureaplasma spp.…”
Section: Discussionsupporting
confidence: 61%
“…and Mycoplasma spp. developed EONS in previous studies 25,26 and in our study. In some studies, 27–30 EONS developed in only Ureaplasma spp.…”
Section: Discussionsupporting
confidence: 61%
“…Other studies, however, did not confirm such a correlation [6, 7, 23-28] (Table 1). Similarly, a significant association between prenatal and postnatal Ureaplasma infection and PVL has not been verified so far [6-8, 22, 23, 25, 26] (Table 1). A study addressing long-term neurodevelopmental outcome in preterm infants, however, found intrauterine Ureaplasma infection to be associated with cerebral palsy and psychomotor delay at the age of 24 months [26].…”
Section: Ureaplasma-driven Neonatal Neuroinflammation: In Vivo Datamentioning
confidence: 99%